Oxidation of Citric Acid using Colloidal MnO2 in the Presence of Non-ionic Surfactant Tween-80 - Iqubal, Dr. S. M. Shakeel (Asian Journal of Pharmaceutics (AJP), 2022)
Introduction: In the geochemistry of the ocean, MnO2 is a significant phase. It has a significant role in the formation of hydrous iron oxide and manganese nodules. Materials and Methods: The UV-Vis spectrum at 390 nm was used to characterize water soluble colloidal MnO2. Non-ionic surfactant such as Tween 80 used for this investigation. Results and Discussion: The kinetics of the oxidation of citric acid by water soluble colloidal MnO2 in the presence of Tween-80 surfactant have been reported for the 1st time. There is no effect of ionic surfactants CTAB and SDS. The reaction proceeds through the adsorption of lactic acid on the surface of the colloidal particles. Conclusion: The non-ionic surfactant Tween-80 showed a catalytic effect up to certain concentrations thereafter an inhibitory effect follows. Non-ionic surfactant Tween-80 by bringing the reactants close and closer due to multiple hydrogen bonding. In doing so rate increased.